Choose love - Davies, Nicola 1958- (Graffeg, 2022)
Choose Love is a cycle of poems that highlights the experience of those forced to become refugees. The core of the collection was written in 2018 as part of a project with the charity Refugee Trauma Initiative. With the permission of both individual refugees and aid workers, RTI shared with Nicola a number of true and poignant stories which were then used as the basis for short-form poems. Over the following years Nicola has added to this core of poems to create a coherent collection on the theme of forced migration, its wider causes and consequences
Keywords: Kinderlyrik; Englisch; Flüchtling; Political refugees / Juvenile poetry; Refugees / Juvenile poetry; Political poetry, English; Réfugiés / Poésie pour la jeunesse; Poésie politique anglaise; Children's poetry, English; Bilderbuch